FEATURES OF EARLY POSTNATAL ADAPTATION IN PREMATURE INFANTS WITH EXTREMELY LOW AND VERY LOW BODY WEIGHT IN THE PRESENCE OF A FUNCTIONING PATENT DUCTUS ARTERIOSUS AT BIRTH - Жанна Анатольевна Звягина; Людмила Николаевна Игишева; Елена Глебовна Цой; Наталья Степановна Черных (The Publishing House Medicine and Enlightenment, 2023)
The aim of the research - to study the features of postnatal adaptation in children with extremely low and very low body weight with a functioning arterial duct in the early neonatal period. Materials and methods. A continuous prospective study included 98 children with extremely low (ELBW) and very low body weight (VLBW) at birth, with a gestation period of 23-35 weeks, and a birth weight of 540-1500 g. Clinical and anamnestic data, parameters of neurosonography and hemodynamic significance of the arterial duct arteriosus (AP), as well as the values of the level of neuromarkers (S100, NSE), the level of NT proBNP in the early neonatal period were studied. Blood sampling for the study of neuromarkers and NT proBNP was carried out once in the early neonatal period. Results. In the vast majority of deeply premature newborns in the early neonatal period, ductus arteriosus continues to function (68.36 %). The persistence of ductus arteriosus is significantly characteristic of premature patients with a burdened antenatal history (obesity and sexually transmitted infections (STIs)). Premature patients with functioning ductus arteriosus  are characterized by birth at an earlier gestation period, but with a higher body weight relative to this gestation period, compared with newborns whose ductus arteriosus  was closed by 72 hours. Premature infants with ductus arteriosus  are characterized by: respiratory acidosis and the development of pulmonary tissue atelectasis. The values of NTproBNP and NSE and S100 (marker of perinatal damage to the central nervous system) were within the reference values in all studied premature infants and did not differ in the groups. The functioning of the arterial duct is characteristic of deeply premature infants with a burdened antenatal period due to the somatic pathology of the mother, who have pronounced respiratory disorders. Persistence of the ductus arteriosus in the early neonatal period in premature infants with ELBW and VLBW did not lead to an increase in NTproBNP and NSE and S100.